Tatakelola Kerajaan yang Baik (Good Governance): Gerakan Islam dan Rashid Al-Ghannouchi - Maszlee Malik; Hamidah Mat (Universiti Sains Islam Malaysia, 2024)
Good Governance has become a fad du jour concept in the discourse of development in recent time. Unfortunately, the practice of Good Governance concept is not viable in most Muslim countries. Poor practice of governance in many Muslim countries implies the importance of the topic ‘Good Governance’ to be further explored. This article will focus its study on Islamic point of view towards Good Governance based on Rashid Ghannouchi’s perspective on governance. It will analytically looks into Rashid al- Ghannouchi’s point of views, due to his position as ideologue and thinker of modern Islamic movement and the application of his views on his Ennahda movement in Tunisia. Studies on al-Ghannouchi’s thoughts in this article will be done through a critical discourse analysis of his books and articles. Field study such as interviews were also conducted. This study found that the concept and practice of good governance as proposed by the international institutions share a lot of similarities with some Islamic concepts.